The effect of cesarean section on the incidence of congenital nasolacrimal duct obstruction - Ulutaş, Hafize Gökben; Uçan Gündüz, Gamze (The European Research Journal, 2021)
Objectives: The aim of this study is to evaluate the effect of cesarean section (CS) on the incidence and recovery of congenital nasolacrimal duct obstruction (CNLDO). Methods: The files of patients diagnosed with CNLDO, epiphora, and dacryocystitis under the age of 24 months were identified retrospectively. Patients were divided into 2 groups according to whether they were born via normal vaginal delivery (VD) or CS. Demographic data, gestational age, birth weight, application of lacrimal massage, and surgical treatment modalities were recorded from medical records. Results: The study included 173 consecutive patients, 68 were females and 105 were males. Eighty-two (47.4%) patients were born via VD and 91 (52.6%) patients were born via CS. The frequency of CS delivery in children with CNLDO (47.4%) was significantly higher than the same hospital’s total frequency of CS delivery (40.2%) (χ2 = 11, df = 1, p = 0.001). At presentation, the mean age of the patients born via CS was lower than patients born via VD (9.4 ± 6.8 months vs 12.07 ± 8.8 months) (p = 0.027). In 40 patients who had a family history of CNLDO, 23 patients recovered through non-surgical treatment, while 17 patients had a surgical intervention, which was found to be statistically significant (p = 0.009). The gestational age and birth weight of patients born via CS were significantly lower than patients born via VD (p < 0.001 and p = 0.01, respectively). Conclusions: Cesarean section delivery could increase the incidence of CNLDO.